APPLICATION OF ELECTRICAL RESISTIVITY METHOD FOR SAFETY EVALUATION OF ASEJIRE DAM IBADAN, SOUTHWESTERN NIGERIA - Oladejo, Olagoke Peter; Ogunkoya, Charles Olubunmi; Fasiku, Taiwo Bukola; Olanrewaju, Surat Alaba (FUDMA JOURNAL OF SCIENCES, 2024)
Dam construction provides economic importance to the environs through, water supply and flood control. Post-construction investigation is however necessary for maintenance stability to avoid irreversible environmental changes. In view of this, horizontal resistivity profiling and vertical electrical sounding (VES) were conducted along the embankments and the downstream of Asejire dam to determine its integrity. The methods used were horizontal resistivity profiling and vertical electrical soundings conducted along the embankments and the downstream. Thirty-one VES and Dipole-Dipole Profiling were occupied along the embankments and downstream using Resistivity meter at 20 m intervals for both the VES and Dipole-Dipole. The Dipole-Dipole data were inverted into 2-D Resistivity Images using DIPPRO™ 4.0 Inversion Software while the VES data were quantitatively interpreted using the partial curve matching technique and Winresist 1.0 Version Software. Results of dipole-dipole image and geo-electric section identified three geo-electric layers; comprising topsoil presumably clayey sand and laterites with resistivity and thickness between 59-760m and 0.7-5.2m respectively. The second layer is weathered layer attributed with clay/clayey sand having resistivity and thickness 18-766m and 3.1-36.7 m. The third layer suspected to be fresh bedrock with resistivity range 121-3672m and 18-766 m thick. The Dipole-Dipole results displayed resistivity less than 500m in the first layer with structural evidence of discontinuous observables, but the underlying sequences displayed no indicative of structural weakness. This significant features play a major role in seepage processes from the dam, therefore lithological composition obtained from these results shows the dam has a good integrity.